Evaluasi Usability pada Aplikasi Sistem Pencatatan Pegawai Menggunakan Metode Usability Testing dan USE Questionnaire - Abraham Timotius Asmoro Putro; Adi Wibowo; Sutikno Sutikno (Department of Informatics, Universitas Diponegoro, 2024)
In the era of increasingly rapid digitalization, employee recording system applications have become an unavoidable necessity for companies for the efficiency and effectiveness of human resource management. In this context, the usability or usefulness of employee management system applications is a crucial factor in ensuring that users can smoothly and efficiently utilize the system provided. Usability is an important aspect in application design that is often overlooked. The success of an application is not only determined by its features and functionality, but also by the ease of use and user satisfaction in operating it. Therefore, usability evaluation is a very necessary step to ensure that the application being developed meets user needs optimally. The usability testing method and the use of questionnaires are common approaches used in evaluating the usability of an application. In the context of the CV. Cupang Semarangan employee recording system application, this study aims to evaluate the usability of the application using the usability testing method and questionnaire. This study resulted in usability values for the aspects of effectiveness, efficiency, ease of use, ease of learning, and satisfaction being 87.96%, 77.47%, 64.88%, 71.43%, and 68.57% respectively.